Switch Therapy Antibiotik Pasien Apendisitis RSUD Arifin Achmad Provinsi Riau - Ayu Rahmawati; Elka Yulinda; Hansen Nasif (LPPM Universitas Abdurrab, 2019)
Has conducted a study entitled Switching Antibiotic Therapy to Cases of Appendicitis Surgery in Functional Medical Staff of Arifin Achmad Regional General Hospital, Riau Province. This type of research is a retrospective data observation study, medical record data of appendicitis surgery patients during 2010. The method used is the census method. Antibiotics - Oral Substitution Therapy (IAOST) Protocol to medical record data of appendicitis surgery patients at surgical SMF Arifin Achmad Hospital, Riau Province, following: a therapeutic switch (+) of 17% (29 cases), a percentage that met the switch therapy criteria and did not occur switch therapy (Î”) of 67% (114 cases), the percentage that did not meet the switch therapy criteria and switch therapy occurred (X) by 6% (11 cases), the percentage that did not meet the switch therapy criteria and no therapeutic switch (V) 17% (17 cases).